A survey of aflatoxin M1 in different milk types in Turkey: risk assessment of children’s exposure - Madali, Berna; Gulec, Atila; Ayaz, Aylin (Progress in Nutrition, 2018)
Background/Aims: Aflatoxin M1 (AFM1) is a potent toxic compound frequently found in milk and dairy products. A high AFM1 incidence in milk and milk products creates an important public health risk due to the fact that milk and milk products are consumed widely by infants and children. The objective of this study was to evaluate children’s exposure to Aflatoxin M1 via dietary milk consumption and to determine the AFM1 levels in different types of various heat treated milk which were sold in Turkey. Methods: In this study, 135 milk samples were analyzed to determine levels of AFM1 by enzyme linked immunosorbant assay (ELISA) test kit (Helica, USA) at 3 different periods of the years (February, May, July). While assessing the exposure levels of children to AFM1, Hazard Index was calculated by using to 80th percentiles of AFM1 levels in milk samples and according to the data of Turkey Nutrition Health Survey (TNHS)-2010 the body weights and roughly consumption levels of milk for different age groups. Results: The results of this study indicated that the mean concentration of AFM1 in milk samples was 8.6±4.57 ng/L. The AFM1 level of pasteurized milk samples was lower than UHT milks. The average AFM1 levels of whole, semi-skimmed and skimmed milk samples were found as 8.2±4.29ng/L, 10.5±5.01ng/L and 6.8±3.61ng/L, respectively. None of the samples exceeded the maximum limit of AFM1 which was established by Turkish Food Codex Regulation on Contaminants in foodstuffs. Hazard Index (HI) values were found to be higher in children under 9 years than in children above 9 years, which indicating a risk to infant health. Conclusion: These results indicated that it was essential to minimize health risk and to reduce AFM1 levels in milk. In addition, sustainable measures should be taken from farm to fork at all stages of the food chain system to prevent the formation of AFB1.